Guidelines on pharmacotherapy in patients with stable angina pectoris - Małek, Łukasz A.; Grabowski, Marcin; Filipiak, Krzysztof J.; Opolski, Grzegorz (Przewodnik Lekarza/Guide for GPs, 2006)
New guidelines on the management of stable angina pectoris (including syndrome X and vasospastic/variant angina) were announced last May by the European Society of Cardiology. This article comments on current pharmacotherapy guidelines which concentrate on two main aims: (a) pharmacological therapy to improve prognosis and (b) pharmacological treatment of symptoms and ischaemia. General management issues and indications for revascularization are also shortly described.